TEN YEARS OF THE DEPARTMENT OF EUROPEAN INTEGRATION IN MGIMO-UNIVERSITY - O. V. Butorina; N. Y. Kaveshnikov (Vestnik MGIMO-Universiteta, 2013)
Ten years anniversary of the Department of European Integration in the MGIMO-University gives an opportunity to sum up Department’s achievements and to define the place of the Department in the Russian academic school of European integration studies. The paper consists of three parts. The first presents history the national school of European Integration Studies, since the department of the European Integration in MGIMO-University is an integral part of this scientific school. Authors identify four periods: the formation period (1957 - 1962), the Soviet period of academic research (1962 - 1985), the Russian period within the framework of growing national and international contacts between researchers (1986 - 2000) and the current period, which is characterized by an integrated research environment and a system of university teaching (since early 2000s). The second part describes the process of establishing of the Department and its teaching methods, based on a multidisciplinary approach, strong interplay between teaching and research and integration into the global environment. Authors outline the process of preparation of the first Russian university textbook on European integration, describe its concepts and present opinions of the referees. The third part provides an overview of research activities of the Department and points at main published monographs.